Characterization of Solution Styrene Butadiene Rubber (SBR) Through the Evaluation of Static and Dynamic Mechanical Properties and Fatigue in Silica-Filled Compound - Lee*, Heung-Goo; Kim, Hyon-Soo; Cho, Sung-Tae; Jung, Il-Taik; Cho, Choon-Tack (Asian Journal of Chemistry, 2013)
This study examined the effects of different types of styrene butadiene rubber (SBR) and blended compounds with various butadiene rubber (BR) ratios. Two areas were considered when selecting the SBRs: microstructure and functionalization. Six types of SBRs were chosen as model polymers and mixed with silica at various SBR/BR ratios. The microstructures, such as the styrene and vinyl contents of SBR, were found to affect the shift in tan d with increasing butadiene rubber, which might be due to the degree of compatibility of the SBR with butadiene rubber. In addition, the functionalization of SBR led to a better dispersion of silica due to the Payne effect, resulting in a low tan d at 70 ºC. On the other hand, the functionalization of SBR also affected the fatigue properties of the compound. Therefore, these should be considered carefully in the design of low-hysteresis compounds with functionalized SBRs.